Addressing Vaccine Hesitancy: Validating the PACV Survey for Croatian Parents - Ana Ćurković; Antonela Matana (Infectious Disease Reports)
Background/Objectives: Vaccine hesitancy, recognized by the WHO as a significant global health threat, undermines vaccination efforts. This study aimed to adapt and validate the Parent Attitudes about Childhood Vaccines (PACV) Survey for Croatian parents to understand vaccine hesitancy better. Methods: A cross-sectional study with 1814 Croatian parents was conducted using the PACV survey, translated using a double-back translation method. The psychometrics of the questionnaire were examined, including content validity, dimensionality, construct validity, discriminant validity, and reliability. Confirmatory factor analysis (CFA) assessed the original model’s validity, but the original model fit poorly, prompting exploratory factor analysis (EFA) to identify latent factors. Reliability was measured using Cronbach’s alpha and McDonald’s omega. Results: EFA identified a five-factor model with factors labeled “Safety”, “Schedule”, “Attitudes”, “Behavior”, and “Trust”. Subsequent CFA confirmed this model with acceptable to good fit indices. Discriminant validity was also confirmed. Reliability analyses indicated high internal consistency, with total Cronbach’s alpha at 0.926 and McDonald’s omega at 0.931. Conclusions: The adapted PACV is a valid and reliable tool for identifying vaccine hesitancy among Croatian parents. This study revealed high vaccine hesitancy among Croatian parents, emphasizing the need for targeted interventions.